Práticas pedagógicas coletivas com flauta doce : uma proposta de formação continuada de educadores e educadoras musicais - Ivo, Laís Figueiroa (2017)
In the initial formation of the musical educator, in the context of the undergraduate courses in music, one has the recorder as one of the instruments that can be used by this professional in his teaching performance. Based on the consideration that teacher training should be a permanent process and considering the limitations of instrumental teaching in the initial formation of musical educators, we propose an intervention - the formative activity Recorder and musical education: experiences and reflections - aimed at the continuing education of educators who already use or intend to use the recorder in their classrooms. The activity was elaborated and conducted by the researcher, being offered in the Musicalization Laboratory of the Federal University of São Carlos (UFSCar), between March and May of 2016 and had the participation of twelve educators, in exercise and in initial formation. The objective of the research was to identify and understand educative processes resulting from the intervention proposal. In order to do so, it was supported by theoretical contributions on teacher training and continuing education (GARCÍA, 1999; MIZUKAMI et al., 2002, FREIRE, 1997a and 2009, among others), on training of the musical educator (BELLOCHIO, 2003; DEL BEN, 2003; QUEIROZ; MARINHO, 2005; PENNA, 2007) and on recorder (BARROS, 2010, FRANCISCO, 2015a, 2015b e 2016; CALLEGARI, 2012 e 2013). As a methodological approach, the qualitative approach (DEMO, 2005; BOGDAN; BIKLEN, 1994), action research (THIOLLENT, 2002) and content analysis (BARDIN, 2006; FRANCO, 2008) as method of data analysis. The intervention was elaborated with reference to authors of education and musical education (FREIRE, 1997a; OSTETTO, 2010; FRANÇA; SWANWICK, 2002 and BEINEKE; FREITAS, 2006), seeking a dialogic perspective of the education. The results were organized in two categories - Educative processes with recorder and General educative processes - each containing five units, that analyzed pointed: to the expansion of the perspective of the participants of the pedagogical use of the recorder, implying contributions to their teacher training; for contributions that went beyond this expansion, occurring in the field of interaction and exchanges of knowledge between the subjects, exercising influences on their ways of teaching and learning; for a conception of recorder teaching and training of musical educators and, finally, for the need to carry out further proposals for continuing training with this perspective.